2012
DOI: 10.1007/s10194-012-0475-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex hormonal changes on tension-type headache and migraine: a cross-sectional population-based survey in 2,600 women

Abstract: Sex hormones have some implications on headaches. The objective of the study was to investigate the effects of hormonal changes comparatively on tension-type headache (TTH) and migraine, in a population-based sample. A nationwide face-to-face prevalence study was conducted using a structured electronic questionnaire. 54.3 % of the migraineurs reported that the probability of experiencing headache during menstruation was high, whereas 3.9 % had headache only during menstruation. Forward logistic regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 37 publications
(64 reference statements)
2
55
1
4
Order By: Relevance
“…We equally noted a high improvement rate of 82.5% for TTH. This is higher than the improvement rate of 39.6% reported by Karli et al 14 and the rate reported previously by other authors. 18 Although the precise mechanism for this improvement is not yet elucidated, there is consensus about the role of the level of estrogen and progesterone during pregnancy and their influence on peripheral and central pain transmission via serotonergic, noradrenergic, glutamatergic, GABAergic and opioidergic neurotransmitter systems.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…We equally noted a high improvement rate of 82.5% for TTH. This is higher than the improvement rate of 39.6% reported by Karli et al 14 and the rate reported previously by other authors. 18 Although the precise mechanism for this improvement is not yet elucidated, there is consensus about the role of the level of estrogen and progesterone during pregnancy and their influence on peripheral and central pain transmission via serotonergic, noradrenergic, glutamatergic, GABAergic and opioidergic neurotransmitter systems.…”
Section: Discussioncontrasting
confidence: 60%
“…The modifying effects of hormone on the prevalence of migraine has been well elucidated but not so much for tension type headaches; although it is still thought, that TTH could be influenced by hormonal factors. 14 In terms of improvement, there was a significant improvement rate among the cohort of participants who had migraine and TTH before pregnancy as almost half of these patients had a complete resolution of headaches during pregnancy. The improvement we found is as previously observed with migraine headaches.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The relation of the migraine attacks to the menstrual cycle [117] and to the presence of other non-migraine, chronic pain disorder (lumbago, low-back pain, knee-and hip-joint arthrosis) was also assessed. Depression was not clinically diagnosed in any of the cases.…”
Section: ) Clinical Human Investigationsmentioning
confidence: 99%
“…Migraine attacks are often closely related to female hormonal changes [117]. Hence, it is interesting that PACAP-38-LI increases significantly during the ictal period only in those women whose headache is not related to the menstrual cycle.…”
Section: Menstruation Cyclementioning
confidence: 99%